Strategi Penerapan Komunikasi Penyiaran Islam di Era Society 5.0 - Sri Hertimi; Hamidah Hamidah (Fakultas Dakwah dan Komunikasi, Universitas Islam Negeri, Raden Fatah Palembang, 2022)
Abstract: The development of information and communication which has moved rapidly in the globalization era has influenced the islamic broadcasting communication field, meanwhile islamic broadcasting communication were facing the challenges that need to be faced which is the emergence of Society 5.0. Society 5.0 is the real movement of the development of information and technology that is increasingly sophisticated. This development became a challenge for Islamic broadcasting communication field and all community layers. Therefore, the right breakthrough is needed to face the challenges of Society 5.0. The methodology of this research is a qualitative method using a library research approach. The technique of analyzing the data is an interactive analysis model of Miles and Huberman. The conclusion of this research was done deductively. From the results of the research, the method or strategy for implementing Islamic broadcasting communication in the era of Society 5.0 are firstly, to see the target using three approaches, namely, the religion-based mass media approach, religion group approach, and individual approaches through face-to-face communication or direct communication. The second strategy is using social mobilization. In this approach there are 2 (two) strategies that can be used, namely, lecture and discussion methods. Keywords: Society 5.0; islamic broadcasting communication; implementing strategy